2020
DOI: 10.1111/hsc.12956
|View full text |Cite
|
Sign up to set email alerts
|

Stigma correlates in individuals with mental health conditions versus community members enrolled in a nationwide integrated arts‐based community rehabilitation program in Israel

Abstract: Two of the most prominent challenges faced by people with mental health conditions (MHCs) are experiencing stigma and personal recovery. This study focused on the analysis of baseline data from registrants for integrated arts-based groups in a nationwide psychosocial rehabilitation program in Israel. The aim of the study was to examine the possible associations between self-stigma, personal recovery and creative self-efficacy (CSE) in people with MHCs, and the associations between public stigma, desire for soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…The groups meet weekly for about 2 h and overall group duration ranges between 13 and 36 weeks. A detailed description of the characteristics of participants enrolled in Amitim's arts-based groups is reported elsewhere (Nitzan and Orkibi, 2020).…”
Section: Integrated Arts-based Groups In the Amitim Programmentioning
confidence: 99%
“…The groups meet weekly for about 2 h and overall group duration ranges between 13 and 36 weeks. A detailed description of the characteristics of participants enrolled in Amitim's arts-based groups is reported elsewhere (Nitzan and Orkibi, 2020).…”
Section: Integrated Arts-based Groups In the Amitim Programmentioning
confidence: 99%
“…There is growing recognition of the role played by different art forms in improving health and well-being (Clift and Camic, 2016 ; Fancourt and Finn, 2019 ; Nitzan and Orkibi, 2020 ; Sonke et al, 2021 ), whether as part of everyday life (not for health purposes but with a secondary health benefit), within arts programs designed to promote health, or within specific therapeutic interventions provided by qualified creative arts therapists in various kinds of healthcare settings. The creative arts therapies (CATs) are characterized by the clinical and evidence-informed use of the arts within a therapeutic relationship that relies on experiential and action-based interventions (De Witte et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…The results also confirm previous theoretical proposals and partial empirical findings referring to immigrants, ethnic and sexual minorities or homeless people. Cobarrubias and Han (2011), West et al, (2014) and Nitzan and Orkibi (2020) reported similar relationships with reference to mentally ill people.…”
Section: Main Findingsmentioning
confidence: 69%
“…Authors have analysed intergroup anxiety toward different out‐groups, such as ethnic and racial minorities (Aberson & Haag, 2007; Jasinskaja‐Lahti et al., 2011), sexual minorities (Castiglione et al., 2013; Mereist & Poteat, 2015), immigrants (Abbott & Cameron, 2014; Dhont et al., 2011; Voci & Hewstone, 2003), homeless people (Abersosn & McVean, 2008), disabled (Keith, Bennetto, & Rogge, 2015; Vezzali & Giovannini, 2012) and mentally ill persons (Nitzan & Orkibi, 2020; West et al., 2014). In most of these studies, as a measure of intergroup anxiety, participants rated the degree to which they would experience emotional states such as feeling anxious, relaxed, comfortable, apprehensive, nervous or confident, when fictitiously interacting with persons of the out‐group.…”
Section: Introductionmentioning
confidence: 99%